2021
DOI: 10.1021/jacs.1c05348
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Mediated Ring-Opening and Porphyrin Deconstruction via Conformational Distortion

Abstract: The breakdown of macrocyclic compounds is of utmost importance in manifold biological and chemical processes, usually proceeding via oxygenation-induced ring-opening reactions. Here, we introduce a surface chemical route to selectively break a prototypical porphyrin species, cleaving off one pyrrole unit and affording a tripyrrin derivative. This pathway, operational in an ultrahigh vacuum environment at moderate temperature is enabled by a distinct molecular conformation achieved via the specific interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Our data provide no indication for an organometallic intermediate (C−Ag−C) in the coupling of the porphyrin macrocycles, in contrast to reports on Cu(111) 33 and Cu(110) 39,40 describing an organometallic (C−Cu−C) stage, which may not transition to a C−C bond. Furthermore, no peripheral dehydrogenation, which is expected to modify the STM and AFM contrast, 41,42 is discernible in the observed reaction products.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Our data provide no indication for an organometallic intermediate (C−Ag−C) in the coupling of the porphyrin macrocycles, in contrast to reports on Cu(111) 33 and Cu(110) 39,40 describing an organometallic (C−Cu−C) stage, which may not transition to a C−C bond. Furthermore, no peripheral dehydrogenation, which is expected to modify the STM and AFM contrast, 41,42 is discernible in the observed reaction products.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…This lack of change in the N adsorption height may suggest that it is more dictated by interactions with the underlying surface, rather than “pulled down” into the surface by the metal center. Indeed, Cu has a strong affinity to molecular N, which has previously been seen to result in the significant distortion of tetraphenyl porphyrins on this surface. , …”
Section: Discussionmentioning
confidence: 95%
“…This finding is reminiscent of bond-resolved AFM data on selected metalated tetrapyrroles, featuring a central depression (e.g., planarized Zn-porphyrin, 77 square-type Zn-porphyrin tetramers, 78 Zn-Pc/NaCl 79 Ag-Pc/ Ag(111), 80 and CuPorA2 21 ), whereas other metalated, as well as free-base, tetrapyrroles show faint cross-like signatures at the macrocycle center. 18,21,23,26,60 Generally, the contrast is influenced by electrostatic interaction between the COfunctionalized tip and the central ion (expected to be attractive for Zn 2+ ) and by Pauli repulsion affected by the d-orbital occupancy and the vertical position of the atom/ion. AFM image simulations based on the DFT-optimized geometry (see Scheme 1) indeed reflect these competing contributions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In the reported on-surface coupling reactions, the R–X functional group is activated and subsequently cleaved, forming a monoradical intermediate R· via the dissociation of X·. , In contrast, the ring-opening of a functional group could produce a diradical intermediate through the cleavage of the ring, which may bring new reaction modes that result in the formation of novel polymers. For example, the heterocyclic ring-opening reactions, such as on-surface desulfurization of thiophene, deconstruction of porphyrin and N -doped nanographene, and the ring-opening polymerization of melamine, have been reported to generate a variety of novel nanostructures. Recently, Gao et al reported a debromination ring-opening coordination reaction of hexabromobenzene to synthesize C6–Ag organometallic polyyne …”
Section: Introductionmentioning
confidence: 99%